NILAI PENDIDIKAN AKHLAKDALAM AL-QUR’ANSURAH AL-ISRA’ AYAT 23-27 DAN RELEVANSINYA DIERA REVOLUSI INDUSTRI 5.0 - Putri Syahri; Muhammad Fahrezi; Wuri Tamtama Abdi; Fahruddin Azmi (Reflektika, 2019)
The purpose of this research is to ascertain whether the moral education espoused in Surah Al-Isra' verses 23-27 is relevant in today's society, which is marked by a greater degree of technical progress. The purpose of this research is to examine the many possible precedents for the moral education principles found in the Qur'an. Research is done at libraries, and it may be done in a number of different ways, such as by collecting data, by reading scientific publications that lead to the topic of study, or by obtaining literary data. The value of moral education, as addressed in Al-Isra' verses 23-27, is examined using semiotic analysis, and the results show there may be a relationship between the importance of moral education and the development of the fifth industrial revolution. In particular, verses 23–27 of Surah Al-Isra' stress the following characteristics of moral education as comprising the value as mentioned therein: a) Respect for one's parents (ihsan) and avoiding making false claims about Allah are examples of Allah-honoring morals. b) Humility towards one's parents and regular prayer on their behalf are moral obligations. c) The duty to serve one's parents with integrity and to apologise to them for any wrongdoing on one's part. d) Let's make things simpler for our needy family. e) Adopting a frugal lifestyle and not wasting money or resources, which is important in the post-"4.0" era of industrialization: a) Changes in how individuals usually interact with one another. b) how far apart they keep themselves socially in modern society. c) Changes in conventional social practises. d) Changes in the accepted standards of hospitality in modern culture. e) Results and changes in people's social behaviours